EVALUASI KINERJA PELAYANAN PEGAWAI PERPUSTAKAAN DI KANTOR DINAS KEARSIPAN DAN PERPUSTAKAAN PROVINSI GORONTALO - Manangin, Yulmi; Mozin, Sri Yulianty; Tohopi, Rustam (Politeknik STIA LAN Makassar, 2024)
This research aimed to analyze & depict employee performance in library services at the Gorontalo Province Archives and Library Agency Office, studied from the perspectives of 1) productivity, 2) service quality, 3) responsiveness, 4) responsibility, and 5) accountability. This research employed qualitative methods with descriptive approach. According to the research findings, it can be concluded that the performance of employees in library services at the Gorontalo Province Archives and Library Agency Office in terms of service quality and responsibility has run optimally . However, based on the perspective of productivity indicator, employee performance indicated shortages in the number of employee personnel, limited budget allocations, and the availability of book collections that did not meet the established standards, resulting in less effective employee productivity. Meanwhile, the responsiveness indicator showed that some employees were still less responsive to visitor needs, affecting the maximum service quality. Lastly, the accountability indicator denoted that not all employees in the same field were competent in providing information and user guidance services to visitors, causing imperfections in both services.